Microfiber bragg grating with zinc oxide nanorod arrays for temperature sensing / Aisyah Mohamad Aris, Husna Abdul Rahman and Sulaiman Wadi Harun - Mohamad Aris, Aisyah; Abdul Rahman, Husna; Harun, Sulaiman Wadi (Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, 2017)
Previous works utilizing fiber Bragg grating (FBG) for sensing temperature differences often reported on complexity of the design due to the multi-parameter sensor configuration. Sole FBG based temperature sensor on the other hand commonly suffers from limited measurement range and low sensitivity. In this paper, a zinc oxide (ZnO) nanorods integrated silica microfiber Bragg grating sensor is developed for the measurement of temperature ranging from 50°C to 150°C. The spectral responses of the proposed sensor are monitored using optical spectrum analyzer (OSA) to observe its Bragg wavelength shift and are compared with those from bare FBG. When subjected to increasing ambient temperature, the hydrothermally synthesized ZnO nanorod arrays experienced higher thermal expansion and thus, exhibited better performance than its bare counterpart with measured temperature sensitivity of 13.6 pm/C and 10.9 pm/°C, respectively. The sensor resolution also significantly improved due to the growth of ZnO nanorod arrays on the taper surface by reducing the original resolution from 0.48°C to 0.02°C.